Efficacy of single dose of low-level laser therapy on spontaneous pain caused by separators in orthodontic patients: An experimental study - Nawaz, Ramsha; Amin, Erum; Gul, Bushra; Hassan, Mehak Ul (Journal of the Pakistan Medical Association, 2026)
Objective: To investigate the efficacy of single dose of low-level laser therapy with respect to spontaneous pain reduction after orthodontic separator placement. Method: The prospective, randomised, experimental study was conducted at the Department of Orthodontics, Armed Forces Institute of Dentistry, Rawalpindi, Pakistan, from January to June 2023, and comprised patients of either aged 12-22 years who underwent orthodontic separator placement. The patients were randomised into two groups, with those in Group A receiving a single dose of 200mW of non-contact continuous low-level laser therapy buccally on 3 points, and those in Group B receiving light emitting diode light as placebo. Pain was assessed using visual analogue scale at 24, 48 and 72 hours after the insertion of orthodontic separators. Data was analysed using SPSS 24. Results: Of the 60 participants, 30(50%) were in group A; 19(63.3%) females and 11(36.6%) males. There were 30(50%) patients in Group B; 18(60%) females and 12(40%) males. The overall mean age was 14.95±2.09 years. Mean pain levels at 24, 48 and 72 hours were higher in Group B compared to Group A (p<0.05). Gender was not significantly associated with pain (p>0.05) at any time interval. Conclusion: Low-level laser therapy appeared to be effective with respect to spontaneous pain reduction after orthodontic separator placement. Key Words: Low-level laser therapy, Pain perception, Visual Analogue Scale, Orthodontic appliances, Analgesic agents.